FLEXIBLE WORKING ARRANGEMENT DAN PENGARUHNYA TERHADAP WORK-LIFE BALANCE PADA RESELLERS ONLINE SHOP - Reineldis Ina P Hada; Rolland Epafras Fanggidae; Ni Putu Nursiani (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
This study aims to find out how to describe and analyze the effect of flexible working arrangements on work-life balances on  Resellers Online shop  in Kupang City. The method used in research this is a survey method. The instrument used in This research is a questionnaire, interview, and documentation study. The population of this research is, online shop resellers in Kupang city who sell products / goods through Facebook. The sampling technique in this study uses amethod non probability sampling. The results showed that a flexible working arrangement can help balance work and personal life, especially for students, the private sector, employees and other work through descriptive analysis. While the results showed flexible working arrangements and a significant positive effect on the work-life balance on resellers online shop  in the city of Kupang